PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA GAME WORDWALL TERHADAP HASIL BELAJAR SISWA: Studi Eksperimen pada Materi Ekosistem Kelas V SDN Jenggrik 2 Tahun Ajaran 2024/2025 - Nursabila, Alma Fitri; Mahendra, Moefty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Wordwall educational games on the learning outcomes of fifth-grade students at SDN Jenggrik 2 in the ecosystem topic. The research was motivated by low student achievement and the limited use of interactive media in science learning. A quantitative approach with a quasi-experimental design was used. The sample consisted of 27 students in the experimental class and 29 students in the control class. The test instrument consisted of 10 multiple-choice questions that had been validated for reliability. The experimental class applied the PBL model integrated with Wordwall media throughout the learning process, while the control class used conventional lecture-based methods. Data were analyzed using an independent sample t-test with SPSS version 26. Results showed that the experimental class had a mean score of 75.19, higher than the control class with a mean of 62.1. The t-test showed a significance value of 0.001 < 0.05, indicating a significant difference between the two groups. It is concluded that the use of the PBL model assisted by Wordwall has a positive effect on improving student learning outcomes in ecosystem material.